Money as a means of cross-cultural and cross-lingual communication - Bobo-Hojayeva, Adolat (The Lingua Spectrum, 2025)
The article investigates the origins of monetary relations in Rus’, starting with the mention in “The Tale of Bygone Years” (859 AD) of the tribute paid to the Khazars, which was collected “by a silver coin and by a squirrel per smoke.” It analyzes the traditional view on the use of a squirrel pelt as a means of payment, while simultaneously questioning its practical durability. The deep connection between the first monetary units – “skotŭ” (livestock), “kuna” (marten), and “bĕl” (squirrel) – and the world of animals and the fur trade is highlighted. This connection is supported by linguistic parallels: in Turkic languages, for instance, the word “tin” means both “squirrel” and “kopeck,” indicating significant cultural and economic interrelations. The historical division into “fur” (kuna, nogata, rezana) and “silver” payment systems is examined. Particular attention is paid to the Turkic influence on Russian monetary terminology, including key words: “Den’ga” (Russian half-kopeck), which originates from the Turkic “tenge” (coin/money in general) and was borrowed in the 14th century. “Altyn” (six den’ga), whose etymology is presumably linked not to the Tatar word for “gold,” but rather to the Turkic numeral “alty” (six) or the name for a squirrel (“tiyïn”). A comparison of the development of the monetary systems in Rus’ and England is conducted, noting common stages: the use of foreign coins (Byzantine, Arab dirhams), the beginning of domestic minting (Vladimir the Great’s zlatniki and srebreniki), and periods of decline. The etymological analysis concludes with a comparison of the origins of the Russian “ruble” (from “rubit,” meaning to chop, referring to chopped silver ingots) and the English “farthing” (one quarter of a penny).